2003
DOI: 10.2174/0929867033368394
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Extracorporeal Detoxification by MARS Dialysis in Patients with Liver Failure

Abstract: Although liver transplantation has become standard procedure for patients with liver failure, a number of issues in the management of these patients remains to be addressed. Alternative approaches have been tested, such as hepatocytes containing liver-support systems and filtration devices. However, the replacement of detoxification has been difficult, as the majority of toxins accumulating in liver failure is albumin-bound. Albumin dialysis (MARS system) is characterized by the specific removal of albumin-bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In AOCLF, some randomized studies [5,6,8,22] and small case series of MARS-treated patients [25][26][27] have reported favorable effects. However, conflicting reports have also emerged [28] .…”
Section: Discussionmentioning
confidence: 99%
“…In AOCLF, some randomized studies [5,6,8,22] and small case series of MARS-treated patients [25][26][27] have reported favorable effects. However, conflicting reports have also emerged [28] .…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, because the advance of technique of activated charcoal filter and the particles of charcoal became smaller and their surface was processed, the chance of platelet destruction and erythrocyte destruction was He NH et al Three artificial liver support systems in treatment of severe viral hepatitismuch less when the blood flowed through activated charcoal filter, biocompatibility of activated charcoal improved [20] . Therefore, the therapy of hemoperfusion adsorption has again been applied to clinic to treat the liver failure patients [21][22][23] . That 24 patients had an improvement in clinical symptoms temporarily and in liver function indicates hemoperfusion adsorption therapy has a temporary supportive effect on liver failure caused by severe viral hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…This is a mechanical device consisting of a continuous haemodiafiltration module based on an albumin‐impregnated permeable membrane that is able to remove both protein‐bound and water‐soluble toxins in the low and middle molecular weight range 6 . Most of the literature available at present is based on observational and noncontrolled trials, performed in more than 500 patients enrolled for a total of more than 2500 treatments in different clinical settings 7 . The removal of albumin‐bound molecules, such as bilirubin, bile acids, aromatic amino acids and copper, is accompanied by a rapid improvement in neurological status, haemodynamic stability and a better clinical outcome in patients with acute exacerbation of chronic liver failure and acute hepatic failure, but also in hepatorenal syndrome and primary graft non‐function or chronic rejection after liver transplantation 7 ,.…”
Section: Artificial and Bioartificial Devicesmentioning
confidence: 99%
“…Whether there is room for an improvement of albumin‐dialysis performance, based on the concomitant use of isolated hepatocytes to simultaneously replace the missing synthetic and metabolic functions, remains an open question 7 …”
Section: Artificial and Bioartificial Devicesmentioning
confidence: 99%